ERG mediates the differentiation of hepatic progenitor cells towards immunosuppressive PDGFRα+ cancer-associated fibroblasts during hepatocarcinogenesis - Haoran Bai; Xinyu Zhu; Lu Gao; Shiyao Feng; Hegen Li; Xiaoqiang Gu; Jiahua Xu; Chen Zong; Xiaojuan Hou; Xue Yang; Jinghua Jiang; Qiudong Zhao; et al. (Cell Death and Disease)
Abstract Cancer-associated fibroblasts (CAFs) play important roles in the occurrence and development of hepatocellular carcinoma (HCC) and are a key component of the immunosuppressive microenvironment. However, the origin of CAFs has not been fully elucidated. We employed single-cell sequencing technology to identify the dynamic changes in different subsets of fibroblasts at different time points in rat primary HCC model. Inflammation-associated CAFs (Pdgfrα + CAFs) were subsequently identified, which demonstrated a significant correlation with the survival duration of HCC patients and a dual role in the tumour microenvironment (TME). On the one hand, they secrete the chemokines CCL3 and CXCL12, which recruit macrophages to the tumour site. On the other hand, they produce TGFβ, inducing the polarization of these macrophages towards an immunosuppressive phenotype. According to the in vitro and in vivo results, hepatic progenitor cells (HPCs) can aberrantly differentiate into PDGFRα+ CAFs upon stimulation with inflammatory cytokine. This differentiation is mediated by the activation of the MAPK signaling pathway and the downstream transcription factor ERG via the TLR4 receptor. Downregulating the expression of ERG in HPCs significantly reduces the number of PDGFRα+ CAFs and the infiltration of tumour-associated macrophages in HCC, thereby suppressing hepatocarcinogenesis. Collectively, our findings elucidate the distinct biological functions of PDGFRα+ cancer-associated fibroblasts (PDGFRα+ CAFs) within the TME. These insights contribute to our understanding of the mechanisms underlying the establishment of an immunosuppressive microenvironment in HCC, paving the way for the exploration of novel immunotherapeutic strategies tailored for HCC treatment.